Democracy declassified : the secrecy dilemma in national security - Colaresi, Michael P., 1976- (New York : Oxford University Press, 2014)
This title tackles an enduring question of particular current importance: How do democratic governments balance the need for foreign policy secrecy with accountability to the public? This book presents the first evidence that national security oversight institutions, while imperfect, both constrain the executive from abuse and convince members of the public to be less sceptical of investments in security. Democratic foreign policy effectiveness depends not only on executive discretion to keep national security secrets, but also on effective retrospective oversight from outside the executive.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 2, 2014).
Keywords: Official secrets; Government information; Security classification (Government documents); Democracy; National security; Internal security; Government accountability